GENRE TABAQAT - syukri syukri (Studia Sosia Religia, 2020)
AbstractTabaqat genres are types of books which are biographical collections of figures based on generations. The contents of Tabaqat can be in the form of classifications of certain figures who have one or more things in common. A work can choose certain groups such as the jurists, mufassir, sasterwan, Sufi, philosophers, grammarians, judges, chancellors in one particular university and so on as themes. The biographical approach makes this type of work very rich and can contain anything. Biography carries a power of its own because it refers directly to the reality of life, one's behavior, work practices, the methodology adopted, and the techniques that it applies. Keywords: Genre and Tabaqat